Analysis of Reliability and Durability of Machines in Extreme Conditions - Suleymanov, P.H. (Herald of Azerbaijan Engineering Academy, 2023)
The article deals with the issues of studying the problems of reliability and durability of machines and equipment according to literary sources. The received data is analyzed. Some patterns related to the reliability and durability of machines and equipment operated in extreme conditions are discussed. Depending on the task at hand, when testing the reliability of machines and equipment, two types of tests are used: identification and control tests. The collection of data to determine the reliability and durability of machines and equipment is carried out using the relevant standards.